Variasi Sifat Makroskopis dan Mikroskopis Pelepah Kelapa Sawit - Kamaliah Kamaliah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
Macroscopic characteristics of palm oil, the colors green and yellow midrib, including coarse texture, have the impression conjecture include rough, fibrous fiber direction straight, belongs to a class of light wood. Frond palm oil when used as a raw material for making paper will produce paper with tensile strength, the strength of folding and bursting strength which is quite high when seen from the results of standardized physical properties of pulp, because it includes quality class II, and the results of variance treatment fronds of palm aged < 5 years and palm fronds aged > 5 years very significant effect on fiber length, fiber diameter, fiber lumen diameter and fiber wall thickness. The average value dimension palm frond fibers to the fiber length is included in the classification of "Long" (2489.357 m), the diameter of the fiber included in the classification of "Great" (39.827 m), lumen diameter fibers included in the classification of "very large" (25.610 μm), and a wall thickness of fibers included in the classification of "medium" (7,069μm). Values derived fiber dimensions palm fronds are Runkel Ration included in quality classes IV, Weaving Southwestern included in quality class I, Muhlsteph Ration included in quality classes IV, Stiffness coefficient included in quality classes IV and Flexibility Ration included in quality class I. Based the total value of the derivative dimension palm frond fibers which included 375 in class II.